Sistema colaborativo para orientação de agentes de trânsito - Alves, Vinicius Orestes (Universidade do Vale do Rio dos Sinos, 2013)
This paper describes the construction of a crowdsourcing system to help traffic officers. The system's goal is to help the laws to be more respected and give some orientation to the traffic officers about the key places of the city where there are more traffic jams. Anyone can help with information about infractions that are happening, the places where them happen the most, or just traffic issues due, for example: traffic jams, broken semaphores, traffic accidents, etc. The collaborations are saved in the system and they are available to be queried by the traffic officers. This way, traffic officers can see in real-time the issues and infractions that are happening in the city and take an action faster and smarter. The citizen contributes with important information for the general good of society, helping in the maintenance of the traffic and increasing the sense of citizenship. The paper 22 details the challenges encountered in the construction of a crowdsourcing system, the solutions adopted and the results achieved.
Keywords: Sistemas colaborativos; Dispositivos móveis; Android; Crowdsourcing; Mobile devices